ATP synthase inhibitory factor 1 (IF1), a novel myokine, regulates glucose metabolism by AMPK and Akt dual pathways. Issue 12 (31st October 2019) - Lee, Hye Jeong; Moon, Jiyoung; Chung, InHyeok; Chung, Ji Hyung; Park, Chan; Lee, Jung Ok; Han, Jeong Ah; Kang, Min Ju; Yoo, Eun Hye; Kwak, So‐Young; Jo, Garam; Park, Wonil; et al.
Abstract : ATPase inhibitory factor 1 (IF1) is an ATP synthase‐interacting protein that suppresses the hydrolysis activity of ATP synthase. In this study, we observed that the expression of IF1 was up‐regulated in response to electrical pulse stimulation of skeletal muscle cells and in exercized mice and healthy men. IF1 stimulates glucose uptake via AMPK in skeletal muscle cells and primary cultured myoblasts. Reactive oxygen species and Rac family small GTPase 1 (Rac1) function in the upstream and downstream of AMPK, respectively, in IF1‐mediated glucose uptake. In diabetic animal models, the administration of recombinant IF1 improved glucose tolerance and down‐regulated blood glucose level. In addition, IF1 inhibits ATP hydrolysis by β‐F1‐ATPase in plasma membrane, thereby increasing extracellular ATP and activating the protein kinase B (Akt) pathway, ultimately leading to glucose uptake. Thus, we suggest that IF1 is a novel myokine and propose a mechanism by which AMPK and Akt contribute independently to IF1‐mediated improvement of glucose tolerance impairment. These results demonstrate the importance of IF1 as a potential antidiabetic agent.—Lee, H. J., Moon, J., Chung, I., Chung, J. H., Park, C., Lee, J. O., Han, J. A., Kang, M. J., Yoo, E. H., Kwak, S.‐Y., Jo, G., Park, W., Park, J., Kim, K. M., Lim, S., Ngoei, K. R. W., Ling, N. X. Y., Oakhill, J. S., Galic, S., Murray‐Segal, L., Kemp, B. E., Mantzoros, C. S., Krauss, R. M., Shin, M.‐J., Kim, H. S. ATP synthase inhibitory factor 1 (IF1), a novel myokine, regulates glucose metabolism by AMPK and Akt dual pathways. FASEB J. 33, 14825‐14840 (2019). www.fasebj.org